Acute Toxicitystudy of Choline Based Ionic Liquids Towards Danio rerio fish and the Aggregation Behavior of Their Binary Mixtures - Shah, Mansoor Ul Hassan; Nasruddin, Nasruddin; Yusup, Suzana Bt; Moniruzzaman, Muhammad (UI Scholars Hub, 2019)
Marine oil spills are effectively controlled by chemical dispersants. However, the toxicity associated with it reduce its employment in marine environment. To overcome this limitation, the acute toxicity of choline based ionic liquids was evaluated as a potential low toxic variant for oil spill remediation. Further, the aggregation behavior of the individual as well as their binary mixtures was also evaluated by employing tensiometry technique. The half-lethal concentration, LC50on zebrafish (Danio rerio) of three choline based ionic liquids showed that the studied ionic liquids (ILs) fall in the range of “practically nontoxic” ( 100-1000 mg L-1).Various micellar properties showed that a synergistic interaction existed between all the binary mixtures (β < 0, f1and f2